Individuals with a vestibular‐related disorder use a somatosensory‐dominant strategy for postural orientation after inclined stance. (14th August 2016) - Chong, R.; Berl, B.; Cook, B.; Turner, P.; Walker, K.
Abstract : Objectives: The visual, somatosensory, and vestibular systems are critical for establishing a sensorimotor set for postural control and orientation. The goal of this study was to assess how individuals with a vestibular‐related disorder keep their balance following prolonged stance on an inclined surface. We hypothesize that subjects will show greater reliance on the somatosensory system than age‐matched controls as inferred by the presence of a forward postural lean aftereffect following the inclined stance (i.e., a positive response). Results: The results revealed an underlying somatosensory‐dominant strategy for postural control in the vestibular group: 100% of the subjects tested positive compared to 58% in the control group ( P =.006). Conclusion: Individuals with a vestibular‐related disorder use a somatosensory‐dominant strategy for postural orientation following prolonged inclined stance. The implications for the management of this population are discussed.